Routine Oxygen Therapy Does Not Improve Health-Related Quality of Life in Patients With Acute Myocardial Infarction—Insights From the Randomized DETO2X-AMI Trial - Hofmann, Robin; Befekadu Abebe, Tamrat; Herlitz, Johan; James, Stefan K.; Erlinge, David; Yndigegn, Troels; Alfredsson, Joakim; Kellerth, Thomas; Ravn-Fischer, Annica; Völz, Sebastian; Lauermann, Jörg; Jernberg, Tomas; et al. (Frontiers in Cardiovascular Medicine, 2021)
BACKGROUND: After decades of ubiquitous oxygen therapy in all patients with acute myocardial infarction (MI), recent guidelines are more restrictive based on lack of efficacy in contemporary trials evaluating hard clinical outcomes in patients without hypoxemia at baseline. However, no evidence regarding treatment effects on health-related quality of life (HRQoL) exists. In this study, we investigated the impact of routine oxygen supplementation on HRQoL 6-8 weeks after hospitalization with acute MI. Secondary objectives included analyses of MI subtypes, further adjustment for infarct size and oxygen saturation at baseline, and 1-year follow-up. METHODS: In the DETermination of the role of Oxygen in suspected Acute Myocardial Infarction (DETO2X-AMI) trial, 6629 normoxemic patients with suspected MI were randomized to oxygen at 6 L/min for 6-12 hours or ambient air. In this prespecified analysis, patients younger than 75 years of age with confirmed MI who had available HRQoL data by European Quality of Life Five Dimensions questionnaire (EQ-5D) in the national registry were included. Primary endpoint was the EQ-5D index assessed by multivariate linear regression at 6-10 weeks after MI occurrence. RESULTS: 3,086 patients (median age 64, 22% female) were eligible, 1,518 allocated to oxygen, 1,568 to ambient air. We found no statistically significant effect of oxygen therapy on EQ-5D index (-0.01; 95% CI: -0.03 to 0.01; p=0.23) or EQ-VAS score (-0.57; 95% CI: -1.88 to 0.75; p=0.40) compared to ambient air after 6-10 weeks. Furthermore, no significant difference was observed between the treatment groups in EQ-5D-dimensions. Results remained consistent across MI subtypes and at 1-year follow-up, including further adjustment for infarct size or oxygen saturation at baseline. CONCLUSIONS: Routine oxygen therapy provided to normoxemic patients with acute MI did not improve HRQoL up to one year after MI occurrence. REGISTRATION: ClinicalTrials.gov number, NCT01787110